The Effect of Logotherapy on the Empowerless of Clients with Chronic Diseases - Rokayah, Cucu (Media Karya Kesehatan, 2024)
Powerlessness is caused by physiological factors, medication management, process of loss, lack of  knowledge,  social  issues, uncertainties and culture. Powerlessness can  stimulate  heplessness and  suicide. The purpose of  this study is to provide an overview of  logoterapy to  clients with powerlessness  problem wich is caused by chronic illnes in the community. The quasi-experimental study on 16 respondents with chronic ilness with intruments of sign and symptoms of helplessness anda the ability to mean life. The result of the study before and after the logoterapy showed a difference in decrease in signs and symptoms of helplessness 30.41 % of cognitive, affective, physical, behavioral anda affective response. Logotherapy is recommended for  client with powerlessness problem  with Chronic illness. In order to increase the effectiveness of logotherapy,  combination therapy is needed for clients with powerlessness. Keywords: Powerlessness, logotherapy, chronic illness.